Analisis dampak korupsi terhadap pembangunan ekonomi di Indonesia - Febriyantie, anya Amelya (Maliki Interdisciplinary Journal, 2026)
Corruption is one of the greatest structural challenges hindering Indonesia’s economic progress. This study aims to analyze in depth the impact of corruption on Indonesia’s economic development from various dimensions, including economic growth, foreign investment, social inequality, the quality of public services, and the stability of the banking system. Using a descriptive qualitative approach based on a literature review, this research examines various scientific sources, reports from international institutions such as Transparency International and World Bank, as well as statistical data from Badan Pusat Statistik (BPS). The findings indicate that high levels of corruption consistently hinder national economic growth, reduce the investment climate, worsen income inequality, weaken the quality of infrastructure and public services, and threaten banking stability. Comprehensive anti-corruption efforts through strengthening supervisory institutions, budget transparency, and bureaucratic reform are key to accelerating sustainable economic development in Indonesia.